Not feeling sick from breast cancer: A framework on health status perceptions transition process. (June 2016) - Hébert, Maude; Gallagher, Frances; St-Cyr Tribble, Denise
Abstract: Purpose: In what state of health do women with breast cancer consider themselves to be? Health professionals classify them as cancer victims but few studies have examined women's perceptions of their own health following a breast cancer diagnosis. We looked at the transition in health status perceptions between before and after receiving the diagnosis. Methods: A grounded theory design was chosen to develop a framework. Results: From an analysis of semi-structured individual interviews with 32 women, it emerged that 1) over a two-year period, the participants went through four iterative steps between receipt of the official diagnosis and the return of the level of energy once the treatments are done. Theses four steps are: reacting emotionally, facing the situation, constructing a new identity and reacting to social representations of cancer, 2) the participants did not feel sick from breast cancer. Conclusion: This study shows learning to live with a sword of Damocles over the head during the transition process. The emergent steps of the health status perceptions transition process in breast cancer trajectory give direction for care. Highlights: This transition from a state of health to a modified state of health is characterized by 'not feeling sick from breast cancer'. The transition process is composed of four iterative steps. Steps are: react emotionally, face the situation, construct a new identity and react to social representations of cancer. This process lasts two years from the official diagnosis to the end of treatments until the energy level is back. The framework of health status perceptions transition process provides a structure to health care professionals.